Agricultural cooperatives and social empowerment of women: a Ugandan case study - Ferguson, Hilary; Kepe, Thembela (Development in practice, 2011)
This article presents a case study of Manyakabi Area Cooperative Enterprise in south-western Uganda, which shows that benefits from agricultural cooperatives can extend beyond monetary tangibles. We discuss several social factors that women members claimed have improved since they became members of the cooperative, including their confidence, their negotiating skills, the ability to be of service to their communities through transferring skills to non-members, and the ability to take control of certain household decisions when dealing with men. We conclude that these social benefits could be enhanced if they were fully acknowledged as important by agents of change.